Exploring the plankton bacteria diversity and distribution patterns in the surface water of northwest pacific ocean by metagenomic methods - Wang, Yafei; Lin, Hongmei; Huang, Ranran; Zhai, Weidong (Frontiers in Marine Science, 2023)
The study of marine microbial communities is crucial for comprehending the distribution patterns, adaptations to the environment, and the functioning of marine microorganisms. Despite being one of the largest biomes on Earth, the bacterioplankton communities in the Northwest Pacific Ocean (NWPO) remain understudied. In this research, we aimed to investigate the structure of the surface bacterioplankton communities in different water masses of the NWPO. We utilized metagenomic sequencing techniques and cited previous 16S rRNA data to explore the distribution patterns of bacterioplankton in different seasons. Our results revealed that Cyanobacteria, Proteobacteria, Bacteroidetes, and Actinobacteria dominated the microbial communities, accounting for over 95% of the total. During spring, we observed significant differentiation in community structure between the different water masses. For instance, Prochlorococcus and Pseudoalteromonas were primarily distributed in the nutrient-deficient subtropical countercurrent zone, while Flavobacteriaceae and Rhodobacteraceae were found in the Kuroshio-Oyashio mixing zone. During summer, the surface planktonic bacteria communities became homogenized across regions, with Cyanobacteria becoming the dominant group (68.6% to 84.9% relative abundance). The metabolic processes of the microorganisms were dominated by carbohydrate metabolism, followed by amino acid transport and metabolism. However, there was a low relative abundance of functional genes involved in carbohydrate metabolism in the Kuroshio-Oyashio mixing zone. The metagenomic data had assembled 37 metagenomic-assembled genomes (MAGs), which belong to Proteobacteria, Bacteroidetes, and Euryarchaeota. In conclusion, our findings highlight the diversity of the surface bacterioplankton community composition in the NWPO, and its distinct geographic distribution characteristics and seasonal variations.